Neurocognitive training enhances the outcomes of children with attention deficit hyperactivity disorder: A preliminary study. - Buker, Nurullah; Karagoz, Ezgi; Sengul, Yesim Salik; Guney, Sevay Alsen; Ozbek, Aylin (Child: Care, Health & Development, 2024)
Background: Attention deficit hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder characterized by diverse clinical manifestations including inattention, hyperactivity and impulsivity. Objective: The present study aims to investigate the effects of neurocognitive training (NT), a personalized and specialized exercise programme on symptoms, attention and dynamic balance in treatment‐naïve children diagnosed with ADHD. Methods: Fourteen treatment‐naïve children aged 7–12 years diagnosed with ADHD were enrolled in the intervention group. The NT intervention was administered weekly for 10 consecutive weeks, supplemented by a structured home exercise programme for 6 days a week over the same 10‐week period. ADHD‐related symptoms, attention and dynamic balance were assessed in pre‐treatment, post‐treatment, 6 months, and 12 months. Fifteen typically developing (TD) children, matched for age, underwent evaluation only once to establish baseline normative values. Results: Following the NT (post‐treatment), significant improvements were observed in hyperactivity‐impulsivity scores, oppositional‐defiant behaviours and dynamic balance when compared to the TD children (p < 0.05). In the ADHD group, a significant difference was found in the long term (12‐month follow‐up) in hyperactivity–impulsivity, oppositional‐defiant behaviours and dynamic balance (p < 0.05). Conclusion: The findings suggest that the NT yields favourable effects on hyperactivity–impulsivity, oppositional defiant behaviours and dynamic balance in children diagnosed with ADHD, with these improvements appearing to be sustained over the long term. Clinical trial registration number: NCT04707040.